Ultrasound Guided Fine Needle Aspiration Cytology of Intra-abdominal Masses in Patients Attending Birat Medical College Teaching Hospital, Nepal - Sinha, Amrita; Singh, Mrinalini; Sedhain, Sapana; Bhattarai, Soorya (Birat Journal of Health Sciences, 2025)
Introduction: Fine needle aspiration cytology is a well-established, rapid, safe and cost-effective diagnostic technique and is increasing in popularity to diagnose mass lesions in intra-abdominal organs. Deep-seated organs are safely sampled and routinely aspirated using the fine needle under radiological guidance. Objective: To diagnose intra-abdominal masses using ultrasound-guided fine needle aspiration cytology and to categorize them as malignant, benign, suspicious, inflammatory, and unsatisfactory according to organ-wise. Methodology: This was a hospital-based prospective cross-sectional study carried out in Birat Medical College Teaching Hospital, where 77 cases were included in which FNAC was done for intra-abdominal masses under ultrasound guidance. Air dried smears were prepared for Giemsa stain and wet smears were prepared for PAP stain. The smears were classified as unsatisfactory, inflammatory, benign, malignant, and suspicious for interpretation categories. Results: A total of 77 patients with intra-abdominal lesions were included in this study. The patient age ranged from 13 to 90 years, out of which 37 cases (48.1%) were males and 40 cases (51.9%) were females. Out of the total 77 cases, 76.6% of cases were reported to be malignant followed by 9.1% inflammatory, 6.5% suspicious, 5.2% inadequate and 2.6% benign. The liver was the most common site for FNAC comprising 35 (45.5%) cases. Conclusions: In cases of intra-abdominal masses, the most common site for FNAC was the liver. Similarly, the most common cytological findings were malignant cases, followed by inflammatory, suspicious, unsatisfactory, and benign cases.